Australian National University. (1934)
Includes articles published between 1934- 1992. Includes articles in Folder 1 on the Canberra University College (CUC), a tertiary education institution established in Canberra by the Australian government and the University of Melbourne in 1930. The College operated until 1960 when it was amalgamated with the Australian National University. The CUC became the School of General Studies at the ANU.
Keywords: Canberra University College; Australian National University -- School of General Studies; Australian National University -- History; Universities and colleges -- Australian Capital Territory -- Canberra; Canberra College of Technical and Further Education; Australian